Tissue-type plasminogen activator protects the postsynaptic density in the ischemic brain. Issue 11 (November 2018) - Jeanneret, Valerie; Ospina, Juan P; Diaz, Ariel; Manrique, Luis G; Merino, Paola; Gutierrez, Laura; Torre, Enrique; Wu, Fang; Cheng, Lihong; Yepes, Manuel
Cerebral ischemia causes the presynaptic release of tissue-type plasminogen activator (tPA). The postsynaptic density (PSD) is a postsynaptic structure that provides a matrix where signaling transduction of excitatory synapses takes place. The postsynaptic density protein-95 (PSD-95) is the most abundant scaffolding protein in the postsynaptic density (PSD), where it modulates the postsynaptic response to the presynaptic release of glutamate by regulating the anchoring of glutamate receptors to the PSD. We found that tPA induces the local translation of PSD-95 mRNA and the subsequent recruitment of PSD-95 protein to the PSD, via plasminogen-independent activation of TrkB receptors. Our data show that PSD-95 is removed from the PSD during the early stages of cerebral ischemia, and that this effect is abrogated by either the release of neuronal tPA, or intravenous administration of recombinant tPA (rtPA). We report that the effect of tPA on PSD-95 is associated with inhibition of the phosphorylation and recruitment of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors to the PSD, known to amplify the effect of the excitotoxic injury, and that this is followed by TrkB-mediated protection of dendritic spines from the harmful effects of the hypoxic insult. These data reveal that tPA is a synaptic protector in the ischemic brain.